2012
DOI: 10.1007/s11010-012-1459-8
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of macrophage-specific functions by oxidized LDL: lysosomal degradation-dependent and -independent pathways

Abstract: Formation of foam cells from macrophages, which are formed by the differentiation of blood-borne monocytes, is a critical early event in atherogenesis. To examine how pre-exposure of monocytes to modified proteins, such as oxLDL, influences their differentiation to macrophages, an in vitro model system using isolated PBMC maintained in culture in the presence of oxLDL was used. Pretreatment of monocytes with oxLDL caused a faster rate of expression of macrophage-specific functions and loss of monocyte-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the present study, our results showed that curcumin significantly reduced MMP-9 and EMMPRIN expression under the stimulation of oxLDL in macrophages, which means that curcumin could be a potential therapeutic agent for inhibiting plaque rupture or retarding atherosclerosis. oxLDL increased EMMPRIN and MMP-9 expression through NF-κB and p38 MAPK pathways and the role of elevated NF-κB and p38 MAPK activity in oxLDL induced atherosclerotic plaque rupture was previous demonstrated (Kojima et al, 2010 ; Yi et al, 2012 ), which is in agreement with other studies (Kim et al, 2001 ; Xie et al, 2011 ; Radhika and Sudhakaran, 2013 ). Results presented here indicated that NF-κB and p38 MAPK is constitutively active in oxLDL stimulated macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, our results showed that curcumin significantly reduced MMP-9 and EMMPRIN expression under the stimulation of oxLDL in macrophages, which means that curcumin could be a potential therapeutic agent for inhibiting plaque rupture or retarding atherosclerosis. oxLDL increased EMMPRIN and MMP-9 expression through NF-κB and p38 MAPK pathways and the role of elevated NF-κB and p38 MAPK activity in oxLDL induced atherosclerotic plaque rupture was previous demonstrated (Kojima et al, 2010 ; Yi et al, 2012 ), which is in agreement with other studies (Kim et al, 2001 ; Xie et al, 2011 ; Radhika and Sudhakaran, 2013 ). Results presented here indicated that NF-κB and p38 MAPK is constitutively active in oxLDL stimulated macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…HOCl-modified low-density lipoprotein leads to unregulated uptake of oxidized low-density lipoprotein into macrophages, followed by their differentiation into foamy macrophages. 57 HOCl oxidizes cardiac myoglobin, which may cause cardiac inflammation and dysfunction in mice after myocardial infarction (MI). 58 HOCl is also shown to have a profound adverse effect on left ventricular remodeling and function after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using 3-MA might have a slight increase in autophagy [35]. To be more clear, we additionally used another autophagy inhibitor CQ, a lysosomal degradation blocker, which could inhibit the fusion of autophagosomes and lysosomes [36,37]. We believe that 3-MA and CQ are more illustrative for our conclusions.…”
Section: Discussionmentioning
confidence: 99%